Acceptance of Teledermoscopy by General Practitioners and Dermatologists in Denmark - Vestergaard, Tine; Andersen, Merethe K.; Bygum, Anette (Dermatology Practical & Conceptual, 2021)
Background: Teledermoscopy can be used to triage referrals of suspected skin cancers, thereby reducing waiting time and number of face-to-face consultations with a dermatologist. However, the success of the implementation of this technology in part relies on the acceptance of the providers.Objectives: This study assessed the attitudes towards teledermoscopy of referring general practitioners and consultant dermatologists.Methods: General practitioners from 48 practices and 3 dermatologists in the region of Southern Denmark, who had previous experience with teledermoscopy, were invited to answer questionnaires on their acceptance of the technology.Results: General practitioners from 23 practices responded. All domains of the questionnaire received high scores, indicating a high degree of acceptance of teledermoscopy among respondents. All 3 dermatologists agreed that teledermoscopy was useful for triaging referrals, but they were less confident in their diagnoses and management plans proposed by teledermoscopy than in traditional face-to-face evaluations of patients. Two of the 3 dermatologists were satisfied with using teledermoscopy as a consult method.Conclusions: This study reports high levels of provider acceptance of teledermoscopy. However, a low response rate among general practitioners may limit its generalizability.